Larval development of indigenous South American freshwater fish species, with particular reference to pacu (Piaractus mesopotamicus): A review - Portella, M. C. [UNESP]; Jomori, R. K.; Leitao, N. J. [UNESP]; Menossi, O. C. C. [UNESP]; Freitas, T. M. [UNESP]; Kojima, J. T. [UNESP]; Lopes, T. S. [UNESP]; Clavijo-Ayala, J. A.; Carneiro, D. J. [UNESP] (Elsevier B.V., 2014)
In recent years, a number of South American freshwater fish have gained increasing attention for their potential in aquaculture, not only because of their excellent performance in farming systems but also to meet the high consumer demand for these species due to declining fishery resources. Many South American freshwater species are migratory and produce altricial larvae, with a small amount of yolk reserves. Unlike precocial freshwater species and altricial coldwater marine fish, these freshwater fish investigated have rapid yolk depletion and metamorphosis. Specific studies on the initial development of South American fish are scarce and fragmented. One of the most widely studied species is the pacu (Piaractus mesopotamicus), farmed in warm continental waters. In the present review we compile new and published data on the initial development of pacu, including morphogenesis of the skeletal, muscle, digestive and sensory systems; compare it to other Neotropical species; and discuss the importance of this information to develop larviculture protocols. When pacu larvae exhaust yolk reserves, they initiate a new form of interaction with the environment, becoming exclusively exotrophic. This type of interaction is made possible by the rapid development of sensory, skeletal, locomotor and digestive structures. In addition to understanding fish ontogeny, studies on larval development are necessary to improve farming systems and larviculture techniques aimed at producing high-quality juveniles in aquaculture. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Piaractus mesopotamicus; Skeletal development; Digestive system; Muscle development; Sensory system; Larviculture